Thyroid cytology during the COVID-19 pandemic: a single centre experience - Kulahci, Ozgur; Tas, Zeynel Abidin (International Surgery Journal, 2021)
Background: In our study, thyroid fine-needle aspiration biopsy (FNAB) data in the same calendar period of 1 year before and after the COVID-19 pandemic were compared. Methods: Thyroid FNAB data for the same calendar period of 1 year before and after the COVID-19 pandemic were included in the study. The patients were grouped according to age, gender and thyroid FNABs according to the Bethesda system for reporting thyroid cytopathology, and the data of both groups were compared considering the diagnoses of the patients who underwent thyroid surgery afterwards. Results: In the post-pandemic period, the number of thyroid FNABs and the number of patients over the age of 40 decreased (all p<0.001). In the post-pandemic period, the rates of atypia of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS), follicular neoplasm or suspicious for a follicular neoplasm (FN/SFN), suspicious for malignancy, and malignant cytology increased despite the decrease in the number of patients (p=0.001). Furthermore, the malignant tumour rate was 1.4% before the pandemic in patients who underwent surgical thyroidectomy and/or lobectomy; this rate was 3.5% in the post-pandemic period (p=0.045). Conclusions: We found an increase in the percentage of AUS/FLUS, FN/SFN, suspicious for malignancy, and malignant cases during the period when there were restrictions, such as pandemics, and the sampling was reduced. This finding is valuable in terms of detecting an increased malignancy rate by performing less thyroid FNAB by carefully determining the indications for thyroid aspiration biopsy regarding the latest guidelines.